Serum lipid profile in patients with oral potentially malignant disorders - P Ramaswamy; Ch Sai Kiran; B Mrudula Raju; M Swathi; A Anusha; Goteti Elizabeth Sharanya (Wolters Kluwer Medknow Publications, 2019)
Aim: To estimate serum lipid profile in patients with oral potentially malignant disorders. Materials and Methods: Around 100 patients with oral potentially malignant disorders and 20 patients as controls were subjected to serum lipid profile after obtaining institutional ethical clearance. Estimation of lipid profile value was done for total serum cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), and triglycerides (TG) using Endpoint method. Results: HDL levels were significantly lower in females with oral potentially malignant disorders (P = 0.047). The mean value of total cholesterol, HDL, VLDL, and TG was lower in leukoplakia compared to lichen planus, smoker's palate, combined leukoplakia, and smoker's palate lesion and oral submucous fibrosis, i.e. 140.78, 32.444, 28.444, 141.33, respectively. The mean value of LDL was low in lichen planus compared to other groups, i.e. 73.167. Conclusion: This study concluded that the lower serum lipid levels might serve as a diagnostic indicator or marker in the early diagnosis of oral potentially malignant disorders in females.